PERKARA PENOLAKAN PEMBATALAN MEREK TERDAFTAR DALAM GUGATAN PERDATA ANALISIS PUTUSAN PENGADILAN NIAGA JAKARTA PUSAT NOMOR 02/MEREK/2002/PN.NIAGA.JKT.PST - Made Dwipayani, Desak; Fazriyah, Nurul (Ganesha Law Review, 2021)
ccording to Article 1 paragraph (1) of Law no. 20 of 2016 concerning Marks and Geographical Indications which determine that a brand is a sign that can be displayed graphically in the form of images, logos, names, words, letters, numbers, color arrangements, in two dimensions and / or three dimensions, sound, hologram, or a combination. of the two or more elements to distinguish goods and / or services produced by persons or legal entities in trading activities of goods and / or services. A registered mark that already has a reputation is often imitated in bad faith by other parties and registered as a trademark. The purpose of this article is to analyze the Decision on the Case for Rejection of the Cancellation of a Registered Mark in a Civil Lawsuit Analysis of the Decision of the Central Jakarta Commercial Court Number 02 / Mark / 2002 / PN.Niaga.Jkt.Pst The method used in this article is normative legal research with reference to Article 21 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications, Books on Intellectual Property Rights, especially Brands. The result of this research is that the Defendant rejects the defendant's lawsuit because it is not proven that the defendant's good faith exists, and the Defendant's trademark registration is in accordance with and complies with the provisions of Articles 4, 5, and 6 of the Trademark Law and there is no substantive similarity between the plaintiff's and the defendant's marks.